Poly(amidoxime) from Polymer-Grafted Khaya Cellulose : An Excellent Medium for the Removal of Transition Metal Cations from Aqueous Solution - Lutfor, M. R.; Sarkar, Shaheen M.; M. M., Yusoff; Kulkarni, Ajaykumar D.; Chowdhury, Zaira Zaman; Md. Eaqub, Ali (North Carolina State University, 2016)
A free radical chain initiation reaction was exploited to prepare poly(acrylonitrile)-grafted Khaya cellulose. The synthesis of the poly(amidoxime) ligand was also performed using oximation reactions. Transition metal cations formed some complexes with the polymeric ligand. The pH of the solution played an important role in the optical detection of Cu2+ ions. The highest absorbance (approximately 94%) of the [Cu-ligand]n+ complex was at pH 6. The sorption quantity increased with increasing Cu2+ ion concentration, which was reflected by a broad peak at 600 nm that was attributed to the charge transfer (- transition) process. The equilibrium sorption capacity of 282 mg/g, with faster adsorption rates (t1/2 = 8 min), suggested that copper possessed excellent adsorption capacity compared with the other cations (Fe3+, Co3+, Cr3+, Ni2+, and Zn2+). The sorption data for all of the cations followed the Freundlich isotherm model, with a high coefficient of determination, reflecting a heterogeneous sorption process by the cellulose-based, poly(amidoxime) adsorbent. The feasibility for recycling of adsorbent was evaluated by the sorption/ desorption study, and the results suggest that a new type adsorbent can be reused in seven cycles without any significant loss in its original sensing and removal performances.